Canola oil and/or linseed oil improved growth performance, immunephysiological and metabolic responses of Nile tilapia: plant oils improved tilapia health - Abdelhamid, AS; Elnokrashy, AM; Ebied, NA; Al-Deriny, SH; Abdelkader, MF; Abozahra, NA; Mohamed, RA (Journal of the Hellenic Veterinary Medical Society, 2024)
This study aimed to evaluate the synergistic effect of canola oil (CO) and linseed oil (LO) on growth performance, blood health, immune-oxidative status, and intestinal morphometry of Nile tilapia, Oreochromis niloticus fingerlings. Fish (n=270, 9.865±0.343g) were randomly distributed in 18 hapas in triplicates at a rate of 15 fish per replicate. Fish were divided into six groups: (1) fish received only basal diet (control group, CG), (2) basal diet containing 0.25% canola oil (CO 0.25%), (3) basal diet containing 0.5 % canola oil (CO 0.5%), (4) basal diet containing 1.0% canola oil (CO 1%), (5) basal diet containing 2% linseed oil (LO 2%), (6) basal diet containing a mixture of canola oil 0.1% and linseed oil 0.1% (CO1 x LO1%). The results showed that the fish that received CO and/or LO had significantly (p<0.05) better growth performance, including final weight, weight gain, specific growth rate, and feed conversion ratio, than CG. The best results were found in fish that received CO/LO. Hematological and biochemical profiles were conducted and showed that dietary CO and/or LO increased red blood cells, hemoglobin, white blood cells, total protein, globulin, cholesterol, triglycerides, and decreased lymphocytes and creatinine compared with CG (p<0.05) with the best findings in CO/LO. Antioxidant enzymes (increased catalase, superoxide dismutase, and reduced malonaldehyde), digestive enzymes (lipase and amylase), immune response (lysozyme and phagocytic index), and intestinal morphometry were improved when fish received CO and/or LO with the best results in CO/LO. To conclude, dietary incorporation of CO and/or LO improved growth performance, blood health, immune-oxidative status, and intestinal morphometry of Nile tilapia fingerlings. The best findings were reported in fish received CO/LO.